Marathon or a Sprint: The United States-Canadian Duel for Specialized Workers in Technology & Modern Employment-Based Immigration Policies At Odds - Chloe N. Bambara (Washington University Global Studies Law Review, 2025)
When competing in a marathon, runners must effectively pace themselves as they propel themselves toward victory—given the enduring nature of the race, a tenacious but calculated stride is critical to success. The global race for technological supremacy is no exception to the rules of marathon running. As of November 2024, China, Canada, the United States (U.S.), and the European Union (E.U.) are among the growing number of global superpowers that have introduced national objectives or directed legislation to increase semiconductor production domestically. The U.S. enacted the CHIPS (formerly “Creating Helpful Incentives to Produce Semiconductors”) and Science Act in 2022, enrolling itself in the international contest for semiconductor production. The Act provides financial support and incentives to domestic producers through the CHIPS for America Fund, among other grants toward research efforts, and explicitly addresses the need for a skilled technical workforce to support the Act’s initiatives. Workforce development is a primary objective in the Act, wherein it seeks to address “STEM workforce gaps.”
Keywords: semiconductor production; Creating Helpful Incentives to Produce Semiconductors; STEM workforce gaps; Employment-Based Immigration Policies; Immigration; STEM visas